Lost in Implementation: Eu Law Application in Albanian Legal System - HAJDINI, Bojana; SKARA, Gentjan (Journal of Legal Studies, 2017)
Considering the growing importance of the researchers in the area of Europeanization in the candidate countries, the purpose of this paper is to analyse whether, and to what extent EU as a legal normative power has influenced Albania to approximate existing and future legislation and to ensure proper implementation. The paper argues that the Europeanization process is pushing Albania toward greater convergence with EU acquis by developing a modern legal framework. However, the paper points out that weak implementation has hampered the application of EU law in Albania due to: a) weak bureaucracy or uneven distribution of human capacities; b) the lack of an established practice of consultation with interest groups on specific draft legislation, and c) the inability to put in sound planning mechanisms and to carry out a realistic assessment. The paper concludes that effective adjustment of Albanian legal system with EU norms requires cooperation between different actors involved in the approximation and implementation process.